PELATIHAN PEMBUATAN E-MODUL MENGGUNAKAN FLIP BUILDER DAN MENGUBAHNYA MENJADI FLIPBOOK PADA GURU IPS UPT SMPN MGMP GUGUS DEWI SARTIKA, KECAMATAN TAPUNG, KABUPATEN KAMPAR - Sri Agustina Ratnawati; Ria Rafianti, Rafly Surya Bagaskara, M. Dwi Afriliansyah (JOURNAL OF COMMUNITY DEDICATION, 2024)
In the field of education today, the use of technology in the learning process has become an indispensable necessity. One way to support learning activities is by utilizing various learning resources, whether in the form of print media or digital media. With technological advancements, teachers are expected to leverage more diverse and adaptive learning resources, such as online teaching materials. One application that can be used to create engaging learning materials is e-modules. Alongside the rapid progress of information and communication technology, educational media need to adapt to modernization, including through the development of digital media based on Flip Builder. The purpose of this community service training is to equip teachers with the skills to use this application, aiming to support the achievement of learning objectives. Flip Builder offers an innovative solution in education by providing a new way to deliver learning materials interactively and engagingly. This training was conducted for Social Studies subject teachers in Public Junior High School Unit the Dewi Sartika Cluster MGMP, Tapung District, Kampar Regency. The conclusions drawn from the training showed that out of 30 teachers participating, 73.33% were able to understand the training materials, 100% found the training beneficial, and 90% felt the training was enjoyable.